Mandatory Ethics Consultation Policy - Romano, Megan E. (Mayo Foundation for Medical Education and Research, 2009)
OBJECTIVE: To describe ethics consultations at a single institution that has a mandatory ethics consultation policy. PATIENTS AND METHODS: We retrospectively reviewed the medical records of all adult patients who were admitted to the intensive care unit at Columbia University Medical Center and had an ethics consultation between August 1, 2006, and July 31, 2007. All mandatory and nonmandatory ethics consultations were reviewed. Patient diagnosis, prognosis, presence of do-not-resuscitate order, presence of written advance directives, reason for the ethics consultation, and survival data were collected. The number of ethics consultations hospital-wide from January 1, 2000, to December 31, 2007, was collected. RESULTS: The total number of mandatory and nonmandatory ethics consultations requested was 168. Of these consultations, 108 (64%) were considered mandatory, and 60 (36%) were considered nonmandatory. Between January 1, 2000, and December 31, 2007, the total number of ethics consultations increased 84%. CONCLUSION: The increase in the total number of ethics consultations is interpreted as a positive outcome of the mandatory policy. The mandatory ethics consultation policy has possibly increased exposure to ethics consultant-physician interactions, increased learning for physicians, and raised awareness among physicians and nurses of potential ethics assistance.